2020
DOI: 10.1038/s41598-020-78627-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between ADHD and physical health: a co-twin control study

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has been associated with increased risk for physical comorbidity. This study used a twin cohort to investigate the association between physical diseases and phenotypic variations of ADHD. A twin cohort enriched for ADHD and other neurodevelopmental conditions were analysed. The Attention Problems subscale of the Child Behavior Checklist/Adult Behavior Checklist (CBCL/ABCL-AP) was used to measure the participants’ severity of ADHD symptoms. Physical health issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Several psychological and medical conditions have ADHD as comorbidity, including mood disorders (e.g., anxiety, depression), substance use disorders, personality disorders, autism, and insomnia [ 17 ]. In addition, neurological and digestive diseases have been associated with ADHD symptomatology as well [ 18 , 19 , 20 ]. As such, it has been suggested that the gut–brain axis may play a common role in in the pathology of both ADHD and these co-occurring diseases [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several psychological and medical conditions have ADHD as comorbidity, including mood disorders (e.g., anxiety, depression), substance use disorders, personality disorders, autism, and insomnia [ 17 ]. In addition, neurological and digestive diseases have been associated with ADHD symptomatology as well [ 18 , 19 , 20 ]. As such, it has been suggested that the gut–brain axis may play a common role in in the pathology of both ADHD and these co-occurring diseases [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, pharmacogenetic studies carried out on children affected by ADHD might not be directly applicable to adults. So far, even though genome-wide association studies offer a powerful means to find the genes involved in different neural activities [ 33 , 35 ], only a small number of loci possibly associated with ADHD have been identified until now [ 19 ]. Taken as a whole, more genetic studies are needed, even for genes that were already investigated in relation to ADHD prognosis (e.g., DRD4, SNAP 25, and COMT) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the treatment response to pharmacotherapy is variable depending on different factors [ 17 ]. Some clinical variables, including age at onset, duration of illness, ADHD presentations, having psychiatric (substance use disorders, major depressive disorder, and personality disorder) and/or neurological (epilepsy and headache episodes) comorbidities, and adherence to treatment, were proposed as possible clinical predictors of treatment response [ 18 , 19 ]. On the other hand, even though no biomarkers were identified as a diagnostic tool for ADHD [ 20 ], some authors tried to detect biological predictors of treatment response in adults affected by ADHD [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical tubers are likely to impact brain development, for example, frontal systems involved in regulatory activities associated with ADHD, which have been associated with cognitive ability in TSC 7 . There is substantial support for the role of epilepsy in ADHD, regardless of cause, 8 and a history of seizures, intractable epilepsy, and epileptic spasms has been associated with ADHD symptoms in TSC 4,9 . Although the limited research to date suggests that the association between TSC and ADHD is likely to be multifactorial in nature, the majority of studies have relied on retrospective report and chart review.…”
Section: Introductionmentioning
confidence: 99%